O IMPACTO DO CAPITAL PSICOLÓGICO E DO SUPORTE ORGANIZACIONAL SOBRE A SATISFAÇÃO NO TRABALHO - Pires Junior, Osvaldo (2015)
The need to obtain and keep the levels of excellence and satisfaction at work increasingly higher take organizations to a growing investments in management models oriented by support of its employees. This scenario takes to some questions: the organizational support affects the employee s satisfaction? Do individuals with higher psychological capital have more satisfaction at work? To try to answer these questions, the study had as a goal to compare and analyze the individual impact and combine of the constructs Organizational Support Perceived, Psychological Capital and Satisfaction at Work. The research was performed with 304 professionals, from public and particular companies, with minimum education equivalent to the average level, of both genders and varying ages. As an instrument to collect data, an autofill questionnaire consisting of three scales: Satisfaction at Work - SAW, Perceived Organizational Support - POS and Scale of Psychological Capital - SPC, will be used. To test the assumptions proposed in the conceptual model, quantitative approach will be used. The collected data will be analyzed by structural equation modeling the PLS algorithm and partials. The results show that the variable Perceived Organizational Support and Psychological Capital impact positively the variable Satisfaction at Work, since that Perceived Organizational Support has more impact on Satisfaction at work that Psychological Capital.